Análisis jurídico doctrinario de la reforma en referencia a la tenencia compartida de niños, niñas y adolescentes en el Ecuador sentencia de la Corte Constitucional No. 28-15- IN/21, ventajas y desventajas - Procel Hidalgo, Soler Del Cisne (2023)
The present work entitled: “Doctrinal legal analysis of the reform in reference to the shared custody of children and adolescents in Ecuador, sentence of the Constitutional Court No. 28- 15-IN/21, advantages and disadvantages”. The interest arises to investigate this problem, since there is a notable legal contradiction in our regulations, because Art. 118 of the Code of Childhood and Adolescence, states that, when the judge deems more convenient for the integral development of the child, he/she will entrust his/her care and upbringing to one of the parents, while in the Constitution of the Republic of Ecuador, in Art. 69 paragraphs 1 and 5, prescribe the promotion of responsible parenthood, particularly when they are separated, and parental co-responsibility in the fulfillment of their duties and rights, even the Code of Childhood and Adolescence in Art. 100, provides for such co-responsibility, in addition to this thanks to Ruling No. 28-15-IN/21 of the Constitutional Court of Ecuador, which by eliminating maternal preference makes the implementation of shared custody viable. In the decisions of the administration of justice regarding separation or divorce trials, it has been possible to observe the violation of the rights of both the children and the parents, since the law stipulates that custody can only be granted to one of the them, limiting to a certain extent the possibility of the judge to grant shared custody, in cases where both parents prove that they are in optimal conditions to take care of all the care that the child or adolescent may require, according to his or her evolutionary development, and they openly state their intention to be an active part of this or her life, as long as the principle of the best interest of the child is guaranteed at all time, so there should not be any legal impediment that hinders the judicial assignment of this type of custody. In this degree word, materials and methods that allowed the development of this research were used, as well as interviews and surveys to legal professionals, whose results were used to propose the legal reform project for the implementation of shared custody in the Code of Childhood and Adolescence.